Obscenity on the Internet: Nationalizing the Standard to Protect Individual Rights - Kagan, Sarah (2010)
This note was written in response to the Ninth Circuit Court of Appeals' 2009 decision in United States v. Kilbride. The Court's opinion called for the application of a national obscenity standard when evaluating speech transmitted online or through e-mail. This note seeks to address some of the practical issues raised by a national standard, including identifying the relevant national community, the need for empirical research on community standards for obscenity, implications for free speech under a national standard and mechanisms to ensure consistent application of a national standard in a diverse country